Spunlaced non-woven material capable of being quickly dispersed and preparation method of spunlaced non-woven material

By mixing the modified mesoporous silicon-based molecular sieve with polylactic acid composite fibers with viscose fibers and wood pulp fibers, the problem of decreasing wet strength of hydrospunlace nonwovens is solved, and a balance between high humidity strength and good fluxability is achieved. Reduced environmental pollution.

CN119162728AActive Publication Date: 2024-12-20ZHEJIANG JINNUO MEDICAL NEW MATERIAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411297398.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

Existing hydrotonic nonwoven materials are difficult to disperse quickly after use, resulting in environmental pollution and sewer blockage problems, and the fiber length is short, the binding force is weak, and the wet strength is reduced.

Method used

The mesoporous silicon-based molecular sieve modified with aminosilane coupling agent and polylactic acid are made by melt spinning to obtain polylactic acid composite fibers, and mixed with viscose fibers and wood pulp fibers to prepare hydrospunlace nonwoven fabrics. The modified mesoporous silicon-based molecular sieve is used to make Capillary action improves the wet strength between fibers, while maintaining good dispersibility under stirring and shearing.

Benefits of technology

It is achieved to improve the wet strength of hydrotonic nonwoven materials without affecting the dispersibility, and to combine good dispersibility and excellent wet strength, reducing environmental pollution and waste accumulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005046454520000061
    Figure BDA0005046454520000061
  • Figure BDA0005046454520000071
    Figure BDA0005046454520000071
Patent Text Reader

Abstract

The invention provides a spunlace non-woven material capable of being rapidly dispersed and a preparation method thereof. The spunlace non-woven material comprises 10-40 wt% of flat viscose fibers, 35-60 wt% of pretreated wood pulp fibers and 20-25 wt% of polylactic acid composite fibers. The polylactic acid composite fiber is prepared by the following method: uniformly mixing an amino silane coupling agent with alcohol, adding a mesoporous silica-based molecular sieve, reacting in a reflux state, cooling to room temperature after the reaction is finished, filtering, washing and drying to obtain a modified mesoporous silica-based molecular sieve; uniformly mixing polylactic acid and the modified mesoporous silicon-based molecular sieve, performing melt spinning, and cutting off to obtain the polylactic acid composite fiber. The interaction between adjacent and contacted fibers can be improved by utilizing the capillary action of modified mesoporous silica-based molecular sieve pores exposed on the surface of the polylactic acid composite fiber when the modified mesoporous silica-based molecular sieve pores encounter water, and the wet strength is improved; due to the fact that the capillary suction force is prone to losing efficacy under the stirring and shearing action and is good in dispersity, the spunlaced non-woven material has good flushability and excellent wet strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonwoven materials, and in particular relates to a rapidly dispersible spunlace nonwoven material and a preparation method thereof. Background Art

[0002] Convenient wet wipes made with spunlace nonwoven technology are increasingly popular among consumers, with about 72% of spunlace nonwovens used for disposable wipes worldwide. However, as landfill and incineration increase urban salt spray and pollution, the post-use treatment of such products is becoming increasingly problematic. Therefore, there is an urgent need for a type of disposable product that can be disposed of without dumping or incineration. An ideal disposal method is to use the urban sewage treatment system and the septic system of individual residences. People are accustomed to throwing nonwoven products into the sewer, and public institutions have to regularly perform equipment maintenance and clear sewers, which has brought a great burden to the social environment. This requires such nonwoven disposable products to have flushability: they are required to have sufficient wet strength during use, disperse in the process of flushing directly into traditional toilets after use, and then be discharged into the sewage system and degraded.

[0003] Fiber raw materials with degradation function, such as wood pulp fiber, viscose fiber, polylactic acid fiber, cotton fiber, cellulose fiber, lyocell fiber, etc., are widely used in the preparation of disposable spunlace nonwoven fabrics. For example, patent CN107419433B discloses a bamboo pulp flushable spunlace material and a production method. The bamboo pulp flushable spunlace material comprises 10-80% by mass of bamboo pulp, 0-60% by mass of wood pulp, and 10-60% by mass of man-made cellulose fiber, which are made by a wet-laid spunlace entanglement process. The gram weight of the bamboo pulp flushable spunlace material is 40-80 g / ㎡. Patent CN102267256B discloses a flushable spunlace nonwoven material and a production method. The present invention discloses a flushable spunlace nonwoven material and a production method which has the properties of high water absorbency, soft hand feel, high strength and can be completely naturally degraded. The material comprises a spunlace nonwoven fabric made of 17mm cellulose fibers, on which a fluff pulp fiber web is spunlace-consolidated.

[0004] The spunlace nonwoven material prepared above not only has the ability to pass through the drainage hole at the bottom of the toilet without clogging the sewer, but also reduces environmental pollution and waste accumulation due to the use of degradable materials. However, in order to obtain excellent flushability, the fiber raw material is short, the bonding force between the fibers is weak, and when the nonwoven fabric is immersed in water, the hydrogen bonds between the fibers will be broken by water, resulting in a significant decrease in the wet strength of the nonwoven fabric.

[0005] Therefore, it is necessary to develop a spunlace nonwoven material having excellent wet strength without affecting flushability. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a fast-dispersible spunlace nonwoven material and a preparation method thereof. First, a mesoporous silica-based molecular sieve modified with an aminosilane coupling agent and polylactic acid are melt-spun to obtain polylactic acid composite fibers, which are then mixed with viscose fibers and wood pulp fibers to prepare spunlace nonwoven fabrics. During the melt spinning and spunlace nonwoven fabric preparation process, the surface pores of the modified mesoporous silica-based molecular sieve are exposed on the surface of the polylactic acid composite fibers. After encountering water, the capillary action of water inside the modified mesoporous silica-based molecular sieve can pressurize the inside of the material, that is, it can improve the interaction between adjacent and contacting fibers and improve the wet strength; and because this capillary suction is easily invalidated under stirring and shearing and has good dispersibility, the fast-dispersible spunlace nonwoven material of the present invention has both good dispersibility and excellent wet strength.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] A rapidly disintegrating spunlace nonwoven material comprises the following raw materials in percentage by weight: 10-40 wt% of flat viscose fibers, 35-60 wt% of pretreated wood pulp fibers, and 20-25 wt% of polylactic acid composite fibers;

[0009] The polylactic acid composite fiber is prepared by a method comprising the following steps:

[0010] (S1) uniformly mixing an aminosilane coupling agent and an alcohol, adding a mesoporous silica-based molecular sieve, reacting under reflux, cooling to room temperature after the reaction, filtering, washing, and drying to obtain a modified mesoporous silica-based molecular sieve for later use.

[0011] (S2) Polylactic acid and modified mesoporous silica-based molecular sieve are uniformly mixed, then melt-spun, and cut to obtain polylactic acid composite fibers.

[0012] In step (S1), the mesoporous silica-based molecular sieve has a particle size of 300-500 nm, an average pore size of 2-10 nm, and a specific surface area of ​​600-1000 m 2 / g. The aminosilane coupling agent is selected from at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, or a combination of two or more thereof. The mass ratio of the aminosilane coupling agent, alcohol, and mesoporous silicon-based molecular sieve is 1:15-25:0.25-0.5.

[0013] In step (S1), the reaction time is 10-24 hours, the washing is 1-3 times with anhydrous ethanol, and the drying temperature is 60-80° C. The mesoporous silica-based molecular sieve is modified by an aminosilane coupling agent to change the surface polarity of the mesoporous silica-based molecular sieve and improve its dispersibility in polylactic acid.

[0014] The alcohol is not particularly limited, and includes but is not limited to ethanol, isopropanol, or a combination of both.

[0015] In step (S2), the melt index of the polylactic acid is 20-30 g / 10 min·210° C. The mass ratio of the polylactic acid to the modified mesoporous silica-based molecular sieve is 100:5-8.

[0016] In step (S2), the melt spinning process includes the following steps: melt extrusion, fiber forming, fiber cooling, winding, stretching and shaping, and filament production; in the process of preparing polylactic acid composite fibers, the amount of modified mesoporous silica-based molecular sieve is critical. Too much will significantly improve the polylactic acid composite fiber's resistance to bending deformation, and the capillary suction is not easy to destroy, resulting in a decrease in dispersibility. Too little cannot improve the wet strength, so this parameter needs to be strictly controlled.

[0017] Wherein: the melt extrusion adopts a single screw extruder with a screw aspect ratio of 24-36, the temperature of zone 1 is 190-210°C, the temperature of zone 2 is 210-220°C, the temperature of zone 3 is 220-250°C, the temperature of the metering pump is 220-250°C, and the temperature of the meltblowing die is 220-250°C. The aperture of the meltblowing die is 0.2-0.35mm and the aspect ratio is 2-4. The screw speed is 30-42rpm, the spinning speed is 2000-3000m / min, the stretching setting temperature is 100-110°C, and the stretching ratio is 1-3.5 times. The fiber cooling adopts air cooling at 15-20°C, the air cooling is 50-120mm away from the meltblowing die, and the air cooling flow rate is 0.5-1m / s.

[0018] The polylactic acid composite fiber has an average diameter of 5-10 μm and a length of 6-12 mm.

[0019] The flat viscose fiber has a fineness of 1.5-2.8 dtex, a length of 10-15 μm, and a width of 1-5 μm.

[0020] The pretreated wood pulp fiber is obtained by adding water to the wood pulp fiber for pulping treatment and drying; the length of the wood pulp fiber is 2-8 mm; the beating degree in the pulping treatment is 40-60°SR, the pulping concentration is 4-5wt%, and the pulping wet weight is controlled at 8.5-9.5g; the wood pulp fiber is selected from one or a combination of coniferous wood pulp fiber and broadleaf wood pulp fiber.

[0021] The present invention also provides a method for preparing the above-mentioned rapidly dispersible spunlaced nonwoven material, comprising the following steps:

[0022] The flat viscose fiber, pretreated wood pulp fiber and polylactic acid composite fiber are opened and mixed to prepare a mixed pulp, the mixed pulp is pumped to the inclined mesh forming system, the wet-laid fiber web is output, the flat mesh is hydroentangled, the drum is hydroentangled, dehydrated, dried and wound.

[0023] The concentration of the mixed pulp is 0.4-1g / L. The flat net hydroentanglement reinforcement process: the water needle is perpendicular to the fiber web, the hydroentanglement pressure is 30-80bar, the diameter of the water needle hole is 0.1-0.15mm, the number of hydroentanglement passes is 3-5, and the amplitude between each hydroentanglement is gradually increased by 5-15bar, the net curtain speed is 5-20m / min, and the hydroentanglement distance is 30-40mm. The rotary drum hydroentanglement reinforcement process: the hydroentanglement pressure is 30-80bar, the diameter of the water needle hole is 0.1-0.15mm, and the number of hydroentanglement passes is 1-3. The dehydration is to remove excess water through a suction device. The drying temperature is 70-130℃, and the drying time is 5-15s.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention firstly uses aminosilane coupling agent modified mesoporous silica-based molecular sieve and polylactic acid to prepare polylactic acid composite fiber through melt spinning, and then mixes the polylactic acid composite fiber with viscose fiber and wood pulp fiber to prepare spunlace nonwoven fabric. During the melt spinning and spunlace nonwoven fabric preparation process, the surface pores of the modified mesoporous silica-based molecular sieve are exposed on the surface of the polylactic acid composite fiber. After encountering water, the capillary action of water inside the modified mesoporous silica-based molecular sieve can increase the pressure inside the material, that is, it can improve the interaction between adjacent and contacting fibers and improve the wet strength; and because this capillary suction is easily invalidated under stirring and shearing action and has good dispersibility, the fast-dispersible spunlace nonwoven material of the present invention has both good dispersibility and excellent wet strength. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.

[0027] Mesoporous silica-based molecular sieve type A MCM-41 was purchased from Shanghai Juna Technology Co., Ltd. with a particle size of 500 nm, an average pore size of 3.4 nm, and a specific surface area of ​​900 m 2 / g.

[0028] Mesoporous silica molecular sieve SBA-15 was purchased from Shanghai Zhenzhun Biotechnology Co., Ltd. with a particle size of 300 nm, an average pore size of 2.0 nm, and a specific surface area of ​​650 m2 / g.

[0029] Polylactic acid spherical particles, with a melt index of 25.1 g / 10 min·210°C, were purchased from NatureWorks, USA.

[0030] The wood pulp fiber is broadleaf wood pulp fiber purchased from Hangzhou Xiangfu Wood Pulp Fiber Manufacturing Co., Ltd., with an average length of 4.1 mm.

[0031] The flat viscose fiber has a fineness of 2.4 dtex, a length of 15 μm, and a width of 3.7 μm, and was purchased from Kelhein, Germany.

[0032] Round viscose fibers of 2.5 dtex and 13 μm in length were purchased from Yamato Spinning Co., Ltd.

[0033] Preparation of fast flushable spunlace nonwoven materials

[0034] Example 1

[0035] (1) 100 parts of 3-aminopropyltrimethoxysilane and 2000 parts of anhydrous ethanol were mixed evenly, 50 parts of mesoporous silica-based molecular sieve MCM-41 were added, the temperature was raised to 70°C, and the reaction was carried out under reflux for 12 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with anhydrous ethanol for 3 times, and vacuum dried at 80°C to constant weight to obtain a modified mesoporous silica-based molecular sieve for use;

[0036] (2) 100 parts of polylactic acid and 8 parts of modified mesoporous silica-based molecular sieve are mixed evenly, and then melt-spinned and cut into polylactic acid composite fibers with an average diameter of 6.5 μm and a length of 10 mm; the melt spinning process includes the following steps: melt extrusion, fiber forming, fiber cooling, winding, stretching and shaping, and filament production.

[0037] Among them: the melt extrusion adopts SJ-30 single screw extruder, the aspect ratio is: L / D=28:1, the temperature of zone 1 is 200℃, the temperature of zone 2 is 220℃, the temperature of zone 3 is 230℃, the temperature of metering pump is 235℃, and the temperature of meltblowing die is 235℃. The aperture of meltblowing die is 0.3mm and the aspect ratio is 4. The screw speed is 35rpm, the spinning speed is 2000m / min, the stretching setting temperature is 100℃, and the stretching ratio is 3 times. The fiber cooling adopts air cooling at 20℃, the air cooling is 80mm away from the meltblowing die, and the air cooling flow rate is 1m / s.

[0038] (3) adding water to 100 parts of wood pulp fibers for pulping, wherein the pulping degree is 47.5°SR, the pulping concentration is 5 wt %, the wet weight of the pulping is controlled at 9.0 g, and drying is performed to obtain dry pretreated wood pulp fibers for later use;

[0039] (4) 15 parts of flat viscose fiber, 60 parts of pretreated wood pulp fiber, and 25 parts of polylactic acid composite fiber were opened and mixed to prepare a mixed pulp with a concentration of 0.4 g / L. The mixed pulp was pumped to the inclined net forming system, and the wet-laid fiber web was output, and the flat net hydroentanglement reinforcement and the drum hydroentanglement reinforcement were performed. The excess water was removed by the suction device, and the fiber was dried at 110°C for 10 seconds and wound to obtain a fiber with a gram weight of 64.5 g / m 2 .

[0040] The flat net hydroentanglement process: the water needle is perpendicular to the fiber net, the first hydroentanglement pressure is 30 bar, the second hydroentanglement pressure is 40 bar, the third hydroentanglement pressure is 50 bar, the fourth hydroentanglement pressure is 55 bar, the fifth hydroentanglement pressure is 60 bar, and the diameter of the water needle hole is 0.12 mm. The net conveying curtain speed is 20 m / min, and the hydroentanglement distance is 40 mm. The rotary drum hydroentanglement process: the hydroentanglement pressure is 40 bar, and the diameter of the water needle hole is 0.12 mm.

[0041] Example 2

[0042] The rest is the same as Example 1, except that in step (1), an equal mass of mesoporous silica-based molecular sieve SBA-15 is used to replace the mesoporous silica-based molecular sieve MCM-41.

[0043] Example 3

[0044] The rest is the same as Example 1, except that the amount of mesoporous silica-based molecular sieve used in step (1) is 25 parts.

[0045] Example 4

[0046] The rest is the same as Example 1, except that the amount of modified mesoporous silica-based molecular sieve used in step (2) is 5 parts.

[0047] Example 5

[0048] The rest is the same as Example 1, except that the amount of modified mesoporous silica-based molecular sieve used in step (2) is 3 parts.

[0049] Example 6

[0050] The rest is the same as Example 1, except that the amount of modified mesoporous silica-based molecular sieve used in step (2) is 10 parts.

[0051] Example 7

[0052] The rest is the same as Example 1, except that, in step (4), 20 parts of viscose fiber, 60 parts of pretreated wood pulp fiber, and 20 parts of polylactic acid composite fiber are opened and mixed to prepare a mixed pulp, the mixed pulp is pumped into the inclined net forming system, the wet-laid fiber web is output, the flat net is hydroentangled, the drum is hydroentangled, the excess water is removed by the suction device, the fiber is dried at 110°C for 10 seconds, and the fiber is wound to obtain a fiber having a gram weight of 63 g / m 2 .

[0053] Example 8

[0054] The rest is the same as Example 1, except that in step (4), 40 parts of viscose fiber, 35 parts of pretreated wood pulp fiber, and 25 parts of polylactic acid composite fiber are opened and mixed to prepare a mixed pulp, the mixed pulp is pumped into the inclined net forming system, the wet-laid fiber web is output, the flat net is hydroentangled, the drum is hydroentangled, the excess water is removed by the suction device, the fiber is dried at 110°C for 10 seconds, and the fiber is wound to obtain a fiber having a gram weight of 64 g / m 2 .

[0055] Comparative Example 1

[0056] (1) 100 parts of polylactic acid were melt-spun and cut into polylactic acid fibers having an average diameter of 6.5 μm and a length of 10 mm;

[0057] (2) adding water to 100 parts of wood pulp fibers for pulping, wherein the pulping degree is 47.5°SR, the pulping concentration is 5 wt %, the wet weight of the pulping is controlled at 9.0 g, and drying is performed to obtain dry pretreated wood pulp fibers for later use;

[0058] (3) 15 parts of viscose fiber, 60 parts of pretreated wood pulp fiber, and 25 parts of polylactic acid fiber were opened and mixed to prepare a mixed pulp, and the mixed pulp was pumped to the inclined mesh forming system, and the wet-laid fiber web was output, and the flat mesh was hydroentangled and the drum was hydroentangled. The excess water was removed by the suction device, and the fiber was dried at 110°C for 10 seconds and wound to obtain a fiber with a gram weight of 65 g / m 2 .

[0059] Among them: Flat net spunlace reinforcement process: the water needle is perpendicular to the fiber web, the first spunlace pressure is 30bar, the second spunlace pressure is 40bar, the third spunlace pressure is 50bar, the fourth spunlace pressure is 55bar, the fifth spunlace pressure is 60bar, and the diameter of the water needle hole is 0.12mm. The net conveying curtain speed is 20m / min, and the spunlace distance is 40mm. Rotary drum spunlace reinforcement process: the spunlace pressure is 40bar, and the diameter of the water needle hole is 0.12mm.

[0060] Comparative Example 2

[0061] The rest is the same as Example 1, except that in step (4), 10 parts of viscose fiber, 60 parts of pretreated wood pulp fiber, and 30 parts of polylactic acid composite fiber are opened and mixed to prepare a mixed pulp, the mixed pulp is pumped into the inclined net forming system, the wet-laid fiber web is output, the flat net is hydroentangled, the drum is hydroentangled, the excess water is removed by the suction device, the fiber is dried at 110°C for 10 seconds, and the fiber is wound to obtain a fiber having a gram weight of 62.8 g / m 2 .

[0062] Comparative Example 3

[0063] The rest is the same as Example 1, except that in step (4), round viscose fibers of equal mass are used to replace the flat viscose fibers.

[0064] The nonwoven materials prepared in the above embodiments and comparative examples were subjected to the following performance tests:

[0065] Dispersibility: The dispersibility test was carried out with reference to the standard JIS P8135-1998. The sample size was 100 mm × 100 mm. It was put into a beaker filled with 300 mL of deionized water and stirred with a magnetic stirrer. The rotor speed was 600 r / min. The dispersion state of the nonwoven fabric was observed visually at regular intervals, and the time required for the nonwoven fabric to be dispersed was determined accordingly.

[0066] If the time to achieve dispersion is 150 s or less, it is considered water-dispersible, and the preferred value is 100 s or less.

[0067] To facilitate result evaluation, the dispersion time and the integrity of the fabric surface after stirring were graded into 6 levels: 0, 1, 2, 3, 4, and 5.

[0068] Level 0: No dispersion after 150s, and the fabric surface is intact.

[0069] Level 1: No dispersion after 100s, dispersion at the edge of the fabric after 150s, but the overall fabric is intact.

[0070] Level 2: It starts to disperse after 100 seconds, and partially disperses after 150 seconds, with a few holes on the fabric.

[0071] Level 3: It starts to disperse after 100 seconds, and is mostly dispersed after 150 seconds, with a large number of holes on the fabric.

[0072] Level 4: Partial dispersion after 100 seconds, and the sample disperses into strips after 150 seconds.

[0073] Level 5: The fabric sample is completely dispersed into lumps within 100 seconds.

[0074] Wet tensile strength: Refer to the standard GB / T 24328.3-2020 Determination of tensile strength, elongation at maximum force and tensile energy absorption of toilet paper and its products. Bend the sample into a ring and immerse it in distilled water or deionized water for 5 minutes. After taking it out, gently wipe off the surface water with filter paper. The sample size is 50mm×150mm, the tensile clamp distance is 100mm, the tensile rate is 50mm / min, the test environment temperature is 20℃ and the humidity is 65%RH.

[0075] Stiffness test: refer to the inclined cantilever method of ZBW 04003-1987 fabric stiffness test method, and cut samples with an area of ​​20cm*2.5cm in the longitudinal and transverse directions for testing.

[0076] Table 1 Performance test results

[0077]

[0078]

[0079] It can be seen from Table 1 that the spunlace nonwoven material prepared by the present invention using flat viscose fibers, pretreated wood pulp fibers, and polylactic acid composite fibers prepared by melt spinning of polylactic acid and modified mesoporous silica-based molecular sieves as raw materials effectively balances the flushability and strength of the spunlace nonwoven fabric, achieving the unity of flushability and strength.

[0080] From the stiffness test results of Example 1 and Comparative Example 3, it can be seen that the spunlace nonwoven material prepared by using flat viscose fibers in the present invention has lower stiffness and is softer.

Claims

1. A spunlace nonwoven material that can be quickly dispersed, characterized in that: The raw materials include the following weight percentages: 10-40wt% flat viscose fiber, 35-60wt% pretreated wood pulp fiber, and 20-25wt% polylactic acid composite fiber; The polylactic acid composite fiber is prepared by a method comprising the following steps: (S1) uniformly mixing an aminosilane coupling agent and an alcohol, adding a mesoporous silica-based molecular sieve, reacting under reflux, cooling to room temperature after the reaction, filtering, washing, and drying to obtain a modified mesoporous silica-based molecular sieve for later use; (S2) Polylactic acid and modified mesoporous silica-based molecular sieve are uniformly mixed, then melt-spun, and cut to obtain polylactic acid composite fibers.

2. The fast-dispersible spunlace nonwoven material according to claim 1, characterized in that: In step (S1), the mass ratio of the aminosilane coupling agent, alcohol, and mesoporous silica-based molecular sieve is 1:15-25:0.25-0.

5.

3. The fast-dispersible spunlace nonwoven material according to claim 1, characterized in that: In step (S1), the mesoporous silica-based molecular sieve has a particle size of 300-500 nm, an average pore size of 2-10 nm, and a specific surface area of ​​600-1000 m 2 / g; the aminosilane coupling agent is selected from at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, or a combination of two or more thereof.

4. The fast-dispersible spunlace nonwoven material according to claim 1, characterized in that: In step (S2), the melt index of the polylactic acid is 20-30 g / 10 min·210° C.; the mass ratio of the polylactic acid to the modified mesoporous silica-based molecular sieve is 100:5-8.

5. The fast-dispersible spunlace nonwoven material according to claim 1, characterized in that: In step (S2), the melt spinning process includes the following steps: melt extrusion, fiber forming, fiber cooling, winding, stretching and shaping, and filament product.

6. The fast-dispersible spunlaced nonwoven material according to claim 5, characterized in that: The melt extrusion adopts a single screw extruder with a screw aspect ratio of 24-36, the temperature of zone one is 190-210°C, the temperature of zone two is 210-220°C, the temperature of zone three is 220-250°C, the temperature of the metering pump is 220-250°C, and the temperature of the meltblowing die is 220-250°C; the aperture of the meltblowing die is 0.2-0.35mm, and the aspect ratio is 2-4; the screw speed is 30-42rpm, the spinning speed is 2000-3000m / min, the stretching and setting temperature is 100-110°C, and the stretching ratio is 1-3.5 times; the fiber cooling adopts air cooling at 15-20°C, the air cooling is 50-120mm away from the meltblowing die, and the air cooling flow rate is 0.5-1m / s.

7. The fast-dispersible spunlaced nonwoven material according to claim 1, characterized in that: The average diameter of the polylactic acid composite fiber is 5-10 μm, and the length is 6-12 mm; the fineness of the flat viscose fiber is 1.5-2.8 dtex, the length is 10-15 μm, and the width is 1-5 μm.

8. The fast-dispersible spunlaced nonwoven material according to claim 1, characterized in that: The pretreated wood pulp fiber is obtained by adding water to the wood pulp fiber for pulping treatment and drying; the length of the wood pulp fiber is 2-8 mm; the beating degree in the pulping treatment is 40-60°SR, the pulping concentration is 4-5wt%, and the pulping wet weight is controlled at 8.5-9.5g; the wood pulp fiber is selected from one or a combination of coniferous wood pulp fiber and broadleaf wood pulp fiber.

9. The method for preparing the rapidly disintegratable spunlace nonwoven material according to any one of claims 1 to 8, characterized in that: The steps include: The flat viscose fiber, pretreated wood pulp fiber and polylactic acid composite fiber are opened and mixed to prepare a mixed pulp, the mixed pulp is pumped to the inclined mesh forming system, the wet-laid fiber web is output, the flat mesh is hydroentangled, the drum is hydroentangled, dehydrated, dried and wound.

10. The preparation method according to claim 9, characterized in that: The mixed pulp concentration is 0.4-1g / L; the flat mesh hydroentanglement reinforcement process: the water needle is perpendicular to the fiber web, the hydroentanglement pressure is 30-80bar, the water needle hole diameter is 0.1-0.15mm, the number of hydroentanglement passes is 3-5, and the amplitude between each hydroentanglement is gradually increased by 5-15bar, the mesh curtain speed is 5-20m / min, and the hydroentanglement distance is 30-40mm; the rotary drum hydroentanglement reinforcement process: the hydroentanglement pressure is 30-80bar, the water needle hole diameter is 0.1-0.15mm, and the number of hydroentanglement passes is 1-3; the dehydration is to remove excess water through a suction device; the drying temperature is 70-130℃, and the drying time is 5-15s.

Citation Information

Patent Citations

  • Dispersible spunlaced nonwoven material and production method thereof

    CN102267256B

  • A water-soluble bamboo pulp spunlace material and its preparation method

    CN107419433B

  • Wallpaper containing a zeolite powder-polylactic acid porous fiber modified acrylic resin emulsion coating

    CN105505079A

  • Toughened and enhanced high-water-absorbent humidifier filter material

    CN106178690A

  • Preparation method for high-strength polylactic acid spun-bonding non-woven material

    CN107574584A

Cited By

  • Viscose fiber absorption core body and preparation method thereof

    CN121242844A

  • Viscose fiber absorbent core and method for manufacturing the same

    CN121242844B